Clinical phenomenology of adaptation disorders in people with computer dependency - Starodubtseva, Yuliia (Journal of Education, Health and Sport, 2018)
To achieve the objective set on the basis of the Kharkov Regional Clinical Psychiatric Hospital No. 3 and in the Military Medical Clinical Center of the Northern region, the complex examination of 147 patients with adaptive disorders were performed (F43.21, F43.22) during 2016-2018. The main group consisted of 85 patients with signs of computer dependence according to the results of AUDIT-like tests; the control group included 62 patients with no signs of addictive behavior. The structure of computer dependence in the examined people of the main group consisted of obsessive surfing (Internet surfing, search for information on databases and search sites) - 45.8% of the surveyed, 22.3 % computer games; 5.8% virtual dating; 14.1% passion for online gambling; 1.2% cybersex (using porn sites). Thus, according to the results of the study, in clinical disorders of adaptation in people with computer dependence mood depression; internal tension with inability to relax; increased susceptibility to previously neutral stimuli; irritability; asthenic symptoms; loss of interest in work or study, family and friends; violation of the sleep- wake cycle are dominated.